Peningkatan Pemahaman dan Kemampuan Pemecahan Masalah Mahasiswa tentang Gizi dan Produktifitas Kerja Melalui Pendekatan Team Based Project dan Berdasar pada Evidence Based Learning di Industri Kerja - Ismi Nurwaqiah Ibnu; Budi Aswin (Jurnal Kesmas Jambi, 2023)
In this very dynamic period, universities must respond quickly and appropriately. Learning transformation is needed to be able to equip and prepare higher education graduates to become a superior generation. In sixteen weeks of meetings, many things can be explored in terms of learning methods, for example direct visits to agencies or companies, analyzing worker nutrition problems by reviewing case studies. This learning inovation to analyze problems and solve problems of nutrition and work productivity in this case juxtaposed with problem base learning (PjBL). This study uses a semi-experimental learning evaluation method with a project-based learning model, with the sample being 7th semester students who take lessons in nutrition and work productivity courses. The duration of this research is during the learning week, which is 16 weeks starting from the odd semester in 2021-2022. The form evaluation of learning outcomes is observational activities in the form of data collection from quiz questions and questionnaires. The application of this model was able to assess the level of student understanding of the work productivity nutrition course. The number of student satisfaction with the evidence based learning and teaching learning model with the Team based project model applied is very high with an average of above 75-85%, and through the results of FGD with student representatives saying that this method is more active, and they do not feel bored in lectures, especially in zoom meetings because they have many activities in learning that are centered on them, not only theoretical explanations from the lecturer.